2011
DOI: 10.3858/emm.2011.43.9.060
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of 4,4'-diaminodiphenylsulfone against paraquat-induced mouse lung injury

Abstract: Although 4,4'-diaminodiphenylsulfone (DDS, dapsone) has been used to treat several dermatologic conditions, including Hansen disease, for the past several decades, its mode of action has remained a topic of debate. We recently reported that DDS treatment significantly extends the lifespan of the nematode C. elegans by decreasing the generation of reactive oxygen species. Additionally, in in vitro experiments using non-phagocytic human fibroblasts, we found that DDS effectively counteracted the toxicity of para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…The importance of Cho et al’s demonstration of TGF-beta mRNA decreases after dapsone (Cho et al 2011 ) meshes nicely with Serizawa et al’s demonstration of enhancement of erlotinib’s effects on non-small cell lung cancer if TGF-beta is simultaneously inhibited (Serizawa et al 2013 ). This also supports a trial of dapsone augmentation of erlotinib.…”
Section: Il-8mentioning
confidence: 76%
See 1 more Smart Citation
“…The importance of Cho et al’s demonstration of TGF-beta mRNA decreases after dapsone (Cho et al 2011 ) meshes nicely with Serizawa et al’s demonstration of enhancement of erlotinib’s effects on non-small cell lung cancer if TGF-beta is simultaneously inhibited (Serizawa et al 2013 ). This also supports a trial of dapsone augmentation of erlotinib.…”
Section: Il-8mentioning
confidence: 76%
“…IL-8 synthesis was also reduced both in LPS stimulated bronchial epithelial cells in vitro (Kanoh et al 2011 ), and in LPS stimulated peripheral blood mononuclear cells (Abe et al 2008 ). Dapsone quantitatively reduced mRNA expression of endothelin-1 (ET-1), macrophage inflammatory protein-1 alpha (MIP-1 alpha), and transforming growth factor-beta (TGF-beta) in a mouse model of paraquat lung injury (Cho et al 2011 ). ET-1 (Kast 2009 ; Liu et al 2011 ; Patel and McKeage 2014 ; Paolillo et al 2010 ), MIP-1 (Fang et al 2011 ; Weigert et al 2009 and TGF-beta (Hau et al 2011 ; Joseph et al 2013 ) are, all three to varying degrees, shown to contribute to many cancers’ growth and treatment resistance, including glioblastoma (Fang et al 2011 ; Stiles et al 1997 ) and EOC (Kast 2009 ; Vergara et al 2010 ).…”
Section: Dapsonementioning
confidence: 99%
“…IL-1 β is a key mediator of the inflammatory response, being involved in a variety of cellular activities, including cell proliferation, differentiation, and apoptosis [ 43 ]. Paraquat has previously been reported to induce the expression of various inflammation cytokines, including TNF- α and IL-1 β , and activate NF-кB [ 44 47 ]. This is consistent with the data presented in this report.…”
Section: Discussionmentioning
confidence: 99%
“… 7 PQ-induced pulmonary fibrosis results from the direct damage caused by oxygen free radicals as well as from the indirect injury caused by inflammatory cells and fibroblasts. 8 10 Moreover, PQ-induced high expression of messenger RNA for pulmonary monocyte chemoattractant protein-1 and macrophage inflammatory protein-1α is responsible for the fibrosis in the lungs. 11 …”
Section: Discussionmentioning
confidence: 99%